Whisker growth in Tasmanian devils (Sarcophilus harrisii) and applications for stable isotope studies. Issue 11 (28th November 2021) - Attard, Marie R. G.; Lewis, Anna; Wroe, Stephen; Hughes, Channing; Rogers, Tracey L.
Abstract: Individual longitudinal records of diet, movement, and physiological state of endangered Tasmanian devils ( Sarcophilus harrisii ) are needed for effective management of wild populations, yet most traditional techniques are expensive or labor‐intensive. Stable isotope analysis of inert tissue, such as vibrissae (whiskers), provides a viable and minimally invasive solution to chronologically record the foraging ecology and habitat use of individuals. Species‐specific information on whisker growth (i.e., time‐position growth of isotopic signatures), retention time, and arrangement on the face is required before the implementation of stable isotope analysis in wild populations. Here, whiskers of six captive Tasmanian devils were internally marked with 13 C‐ and 15 N‐labeled glycine at three‐month intervals followed by isotopic analysis of the longest whisker to provide a time stamp for whisker growth and estimate retention time. Intradermal and extradermal lengths of wild Tasmanian devil whiskers were used to assess the arrangement and relative length of whiskers on the face. We found that whiskers can record at least nine months of an animal's ecological history and that whisker growth is not linear, the growth gradually slows down as the whisker lengthens. Our findings demonstrate that sequentially sampled whiskers have the potential to track monthly and seasonal isotopic changes of an individual animal in the wild, both within its historical range and in areas to which it has recently been introduced. Such information can be used to identify temporal shifts in habitat and prey preferences within populations and help select suitable individuals for translocations. We recommend that the longest mystacial whiskers, positioned posteriorly at the third and fourth row, should be preferentially used for stable isotope studies in this species. The timeframe represented by the root of the whisker (˜3–63 d) can be used to adjust the base of cut whiskers to the correct time period.